Risk equivalent safe operating space as an inclusive framework for living resource management in a multisectoral, multicultural world - Jake Rice; Daniel E. Duplisea; Karen L. Hunter; Marie-Julie Roux (FACETS)
Governance processes for management of living resources are increasingly inclusive and participatory, with more use of integrated risk-based approaches. Progress has been challenged by diverse participants holding different values, evidence rooted in different knowledge systems, and participants placed in adversarial roles. Drawing together developments in risk equivalence, the concept of safe operating space, and viability theory, Risk Equivalent Safe Operating Spaces address these challenges. Within the framework diverse perspectives can express their desired ecological, economic, and social outcomes using their own values and indicators. The aggregate suite of all indicators delineates a multidimensional space within which each perspective can describe their relative risk tolerances along each axis, using evidence from all relevant knowledge systems. The “present state” of the socio-ecological system is identified within this space, along with zones of equivalent risk for each perspective, and (if it exists) a zone of Safe Operating Space (SOS) within some acceptable risk tolerance for all perspectives. Pathways can be developed that first seek equivalent risk for all perspectives, then lead towards the center of the common, shared SOS. Where certain perspectives or dimensions of the multidimensional space have explicit priority, the pathways can prioritize minimizing these risks.